Trading Islamic artworks in seventeenth-century Italy: The case of the Cospi museum - Gigante, F (Gingko Library, 2018)
This essay analyses the influence exerted by mercantile practices on the perception of Islamic artefacts in seventeenth- century Italy. It demonstrates that merchants importing collectibles directly from the Islamic world to Italy also brought information concerning the objects themselves, their cultural backgrounds, and the peoples from whom they originated. At the same time, it establishes that the acquisition of Islamic collectibles outside these Mediterranean trading networks severed the link between the objects and their origins, thus preventing any knowledge of the objects; cultural contexts reaching the Italian collector. Mediterranean mercantile networks therefore emerge as the primary actor in the processes which shaped the perception of Islamic artefacts in seventeenth-century Italy. In this way, the stories these objects told derived in no small part from the biographies they acquired moving from hand to hand. Their original contexts, uses, and narratives were filtered through the numerous people involved at each stage of their journey.